Students’ Perceptions of the Use of Artificial Intelligence (AI) ChatGPT in Foreign Languages Learning (French and German) - Lesmana, Sandy; Kusumaningtyas, Vita; Mala, Nila Viayanti (Peneliti.net, 2024)
The increasing development of technology, followed by the development of science, makes it easier for the world of education to develop knowledge. One example of convenience in the world of education is digitalization. Digitalization makes the learning process completely digital and easier. One form of digitalization in the world of education is Artificial Intelligence (AI) called ChatGPT (Generative PreTrained Transformer) which is used by students in the learning process. This research aims to analyze the responses of French and German students at the Faculty of Language Arts and Culture, Yogyakarta State University to the use of Artificial Intelligence (AI) called ChatGPT (Generative PreTrained Transformer) in the learning process. The object of the research is questionnaire data on the perceptions of French and German students. The data collection method used is the Technology Acceptance Model (TAM) method, namely Actual System Usage (ACU), Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Use (ATU), Behavioral Intention to Use (BI) . The Likert scale was used as a research instrument, namely strongly disagree, disagree, quite agree, agree, and strongly agree. The research results showed that the two highest average ratings obtained from the five indicators were